Menstrual hygiene management among government school going adolescent girls in Tumakuru District, Karnataka in India: a comparative cross-sectional study - Kusuma Achalkar (College of Community Physicians of Sri Lanka, 2024)
Introduction: Menstruation topic remains a taboo subject shrouded  with secrecy and shame among adolescent girls, which leads to lack of discourse and dialogue. Improving menstrual hygie ne management (MHM) practices during adolescent phases reduces reproductive morbidity in future. Objectives: To estimate and compare MHM among urban and rural  government high school adolescent girls Methods: A cross-sectional comparative study was conducted am ong adolescent girls studying in 8th to 10th standard in government high schools. One urban and two rural schools were invol ved in the study to meet the required sample size. In total, 464 girls were assessed using an interviewer-administered que stionnaire. Knowledge and hygienic practices, school absenteeism, restrictions during menses and socio- demographic fa ctors were compared between the two groups. Chi-squared test was used to calculate statistical significance at p<0.05. Results: The girls were in the age group of 12-17 years; mean age of  14.6 (SD=0.92) years with the mean age of attainment of menarche 12.6 (SD=0.94) years. Knowledge on MHM was good  in 157 (62.6%) rural girls compared to 116 (54.5%) urban girls. Pads were the main type of absorbents used by girls (r ural- 128, 51.0%; urban- 167, 78.4%), however, 43% (n=108) rural girls used both cloth and pads during menstruation c ompared to 16.4% (n=35) urban girls. Dysmenorrhea was the common complaint for being absent from school. This  difference between the two groups was significant (p<0.0006). More than 50% of girls in both groups complained that t hey were not permitted to enter ritual places; however, 13.14% (n=28) urban and 22.3% (n=56) rural girls had no restrictions  during menstruation. Conclusions & Recommendations: Girls have less knowledge on m enstruation; many are still using cloth as sanitary pads and do not practice the correct method of washing and drying. A mul ti-pronged approach to improve MHM is essential.